SOME WAYS TO PRESENT OTHER NATIONALITIES – NEIGHBOURS, REPRESENTATIVES OF MINORITIES IN CONTEMPORARY HUNGARIAN CINEMATOGRAPHY - Bubak, Grzegorz (Porównania, 2018)
Hungarian cinema, with only a few exceptions, did not use its chance to offer a full and interesting picture of the Foreigner or the Other that would be devoid of shortcomings. In current movies filmmakers find it very difficult to go beyond established and painful history of prejudices and stereotypes. This applies both to citizens of countries neighbouring with Hungary with which even now it fails to create a correct relationship, and to representatives of numerous national minorities living in the country. The author reviews the images and characteristics of the foreigner which can be found in the contemporary Hungarian cinema and presents problems associated with the creation of a cohesive description of representatives of other nationalities.